Pengaruh Penggunaan Celebrity Endorser, Brand Association dan Brand Image Terhadap Keputusan Pembelian (Studi Kasus Iklan Luwak White Cofee Versi Lee Min Ho Tahun 2016 Pada Pelanggan Luwak White Coffee)" - Halim, Andi Indigo; , Dra. Wafiatun Mukharomah, M.M (2016)
This study aimed to analyze the influence of celebrity endorser, Association brand and brand image of the customer's purchasing decision Luwak White Coffee. Purchasing decisions is an important thing to do a company to know how much the consumer purchase interest in product Luwak White Coffee with the added presence of Lee Min Hoo as a celebrity endorser. One way to achieve a competitive advantage in increasing the purchasing decision is to establish a good brand image in the eyes of consumers and easy to remember always. The data used in this study was obtained from a questionnaire conducted primary and some observation and direct interviews with loyal customers Luwak White Coffee. The analysis technique used is multiple regression using hypothesis testing, the F test and t test. It can be concluded based on the test statistic that variable of celebrity endorser, brand association and brand image together has a positive influence on the purchase decision variable. Based on t test, celebrity endorser, brand association and brand image having an positive and significant impact on the purchase decision. From this study obtained value of Adjusted R Square (R2) of 0.385 (38.5%), which means that the combination of celebrity endorser, brand and brand image Association can explain the impact on purchasing decisions with advertising studies civet coffee white version of Lee Min Ho on customers white civet coffee by 38.5 and remaining influenced by other variables of 61.5%.